2012
DOI: 10.3109/15368378.2011.624660
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of pulsed electromagnetic field as a novel organic pre-sowing method on germination and initial growth stages of cotton

Abstract: Two different pre-sowing techniques have been investigated for their influence in an important industrial plant, namely cotton. Priming methods are very useful for agricultural practices because they improve crop seedling establishment, especially when environmental conditions are not optimum. Pulsed electromagnetic fields have been found to promote germination and improve early growth characteristics of cotton seedlings. Such priming techniques are especially valuable in organic cultivation, where chemical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 19 publications
2
21
0
4
Order By: Relevance
“…The obtained results are in agreement with those of Bilalis et al (2012), who stated that the electromagnetic fields could replace and activate hormones in vegetative growth of oregano as found by Podlesny et al (2005), who recorded that magnetic treatment improved emergence and growth of two pea varieties. Also, Zuhair (2010) showed that spraying strawberry with licorice extract (2 g/L) gave a significant increase in average leaf area, and Qaraghouli and Jalal (2005) found that spraying apple with licorice extract improved all growth parameters and Sheren and Eman (2015) proved that licorice extracts improved growth of Le-Conte "pear".…”
Section: Shoot Length Number Of Leaves/shoot and Leaf Areasupporting
confidence: 82%
“…The obtained results are in agreement with those of Bilalis et al (2012), who stated that the electromagnetic fields could replace and activate hormones in vegetative growth of oregano as found by Podlesny et al (2005), who recorded that magnetic treatment improved emergence and growth of two pea varieties. Also, Zuhair (2010) showed that spraying strawberry with licorice extract (2 g/L) gave a significant increase in average leaf area, and Qaraghouli and Jalal (2005) found that spraying apple with licorice extract improved all growth parameters and Sheren and Eman (2015) proved that licorice extracts improved growth of Le-Conte "pear".…”
Section: Shoot Length Number Of Leaves/shoot and Leaf Areasupporting
confidence: 82%
“…The increase in germination when seeds were magnetically treated could be explained by better availability and absorption of nutrients. Pulsed electromagnetic fields have been found to promote germination and improve early growth characteristics of cotton seedlings [22]. In pea, the investigation of optimal magnetic field doses showed that low magnetic field strength for the longer time of exposure and high magnetic field strength for shorter duration were found to be the most effective in enhancing the growth and yield in the pea cultivar [23].…”
Section: Discussionmentioning
confidence: 99%
“…Low-vigor seeds can be improved using a wide range of treatments, some of them well characterized such as hydropriming and osmopriming. In the context of seed technology, physical methods have showed several advantages over conventional osmopriming protocols ( Bilalis et al, 2012 ). One of the most investigated physical pre-sowing seed treatments in agriculture is based on the use of MFs ( Aguilar et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most investigated physical pre-sowing seed treatments in agriculture is based on the use of MFs ( Aguilar et al, 2009 ). MFs have been described as eco-friendly, cheap, and non-invasive technique ( Bilalis et al, 2012 ; Efthimiadou et al, 2014 ). Additionally, the impact of other types of physical treatments, such as, gamma (γ), and X ionizing, UV, and microwave (MW) radiation will be addressed in this review.…”
Section: Introductionmentioning
confidence: 99%